A First-in-Human Study of CT0590, a Triple Knock-out, Allogeneic CAR T-Cell Therapy Targeting BCMA and NKG2A, in Subjects with Relapsed/Refractory Multiple Myeloma - Fu, Chengcheng; Yan, Lingzhi; Yao, Weiqin; Shang, Jingjing; Jin, Song; Yan, Shuang; Tang, Fang; Zhu, Ziling; Wu, Depei; Li, Ying; Rajakumaraswamy, Nishanthan; Zheng, Wei; et al. (Blood, 2024)
Introduction Autologous chimeric antigen receptor (CAR) T-cell therapies targeting B-cell maturation antigen (BCMA) have been approved for commercial use in patients with relapsed/refractory multiple myeloma (RRMM). However, there are challenges to autologous CAR T-cell therapy which include high cost, time-consuming personalized manufacturing, risk of manufacturing failure, and supply chain logistics. Allogeneic CAR T-cell therapy has the potential to mitigate these challenges. CT0590 is an allogeneic CAR T-cell therapy targeting BCMA and NKG2A (a membrane protein expressed in NK and T cells), and a triple knockout for TRAC/B2M/NKG2A which allows it to avoid graft-versus-host disease (GvHD) and host immune rejection, making it fratricide-resistant while enhancing its immune function. Pre-clinical studies demonstrate that NKG2A-CAR expression facilitates the expansion of CT0590 in the presence of NK cells. Methods This is a first-in-human (FIH), open-label, single center, phase I study of CT0590 in subjects with RRMM to evaluate the safety, tolerability, pharmacokinetics and preliminary efficacy of CT0590 (NCT05066022). Subjects with RRMM treated with ≥ 3 prior regimens (including at least one proteasome inhibitor and one immunomodulatory agent) were enrolled using the i3+3 method for dose escalation. All subjects underwent a lymphodepleting regimen consisting of fludarabine (30 mg/m2) and cyclophosphamide (500 mg/m2) for 3 consecutive days, followed by infusion of CT0590. Results As of 22-Apr-2024, 5 subjects were enrolled (4 subjects with RRMM and 1 subject with primary plasma cell leukemia [pPCL] under compassionate use), with a median age of 54 years (range: 50 to 71 years) and a median of 3 prior lines of therapy. The median time from diagnosis to screening was 2.2 years. Four subjects were double class-refractory and 2 had prior autologous stem cell transplant. At baseline, 2 subjects had ≥ 80% bone marrow blasts, 2 were at ISS stage III, and 4 had high risk cytogenetics. One subject was infused with 0.5 × 108 cells (re-infused with 3.0 × 108 cells), 3 subjects with 3.0 × 108 cells (all were single infusions), and 1 subject with 4.5 × 108 cells (re-infused at the same dose). All 5 subjects experienced Grade 4 cytopenias: Grade 4 lymphocyte count decreased (n=5), Grade 4 neutrophil count decreased (n=5), and Grade 4 platelet count decreased (n=3). Cytokine release syndrome occurred in 2 subjects (1 each at Grade 1 and Grade 2), with a time to onset between 8-10 days after infusion and a duration of 3-4 days. No cases of immune effector cell-associated neurotoxicity syndrome or GvHD were observed. Only 1 subject had Grade 3 treatment-related infection (pneumonia) at Day 12 which fully resolved. No dose limiting toxicities were reported and there were no withdrawal from the study or deaths due to adverse events. With a median follow-up time of 16.6 months (range: 5.1, 24.2), 3 subjects achieved confirmed responses including 2 subjects with stringent complete response (sCR) and 1 subject with partial response (PR). The 2 subjects with sCR include1 RRMM subject [sCR ongoing] with a DOR longer than 23 months as of data cut-off date and 1 pPCL subject with a duration of response (DOR) of 20 months. Another subject achieved PR after a second infusion with 3.0 × 108 cells, but it was not confirmed due to COVID-19. In the 2 subjects with sCR, CAR copies peaked at > 280,000 copies/µg genomic DNA which is comparable to autologous BCMA CAR T-cell products. In the other 3 subjects, the CAR copy numbers were lower or not detected. Due to COVID-19 pandemic, NKG2A expression in NK cells from peripheral blood at screening was only evaluated in 4 subjects, and the results revealed that the two subjects with sCR had higher NKG2A expressions compared to those without sCR. Conclusions Preliminary results of this FIH study of the CT0590 allogeneic CAR T-cell therapy targeting BCMA and NKG2A for the treatment of RRMM demonstrated a manageable safety profile while achieving durable clinical responses. NKG2A expression level at screening may be predictive of clinical response. Enrollment is ongoing to further evaluate the clinical activity of CT0590. Li:CARsgen Therapeutics Co. Ltd.: Current Employment. Rajakumaraswamy:CARsgen Therapeutics Co. Ltd.: Current Employment. Zheng:CARsgen Therapeutics Co. Ltd.: Current Employment. Jiang:CARsgen Therapeutics Co. Ltd.: Current Employment. Liao:CARsgen Therapeutics Co. Ltd.: Current Employment. Li:CARsgen Therapeutics Co. Ltd.: Current Employment.